Jaina vivāha-paddhati : sandarbha, Śvetāmbara Sthānakavāsī (Premarāja Gaṇapatarāja Boharā ; Prāptisthāna A. Bhā. Sādhumārgī Jaina Saṅgha, 1978)
Śvetāmbara Jaina Sthānakavāsī sectàrīan manual of rituals for marriage.